Ureterovaginal fistula: A complication of a vaginal foreign body - Tsia-Shu Lo; Sukanda Bin Jaili; Rami Ibrahim; Chuan Chi Kao; Ma Clarissa Uy-Patrimonio (Elsevier, 2018)
Objective: To know the diagnostic tools and proper management of ureterovaginal fistula following neglected vaginal foreign body in order to achieve optimal outcome. Case report: A case of ureterovaginal fistula associated with a neglected vaginal foreign body. The patient was complaining of a foul-smelling vaginal discharge and lower abdominal pain. On vaginal examination, a hard and large foreign body was found. Examination under anesthesia was performed, and an aerosol cap was removed from her vagina. The patient developed urinary incontinence after removal of the foreign body. Subsequent work-up demonstrated the presence of a right ureterovaginal fistula. The patient underwent an abdominal ureteroneocystostomy. At one year follow up, the patient had fully recovered. Conclusion: Ureterovaginal fistula following neglected vaginal foreign body is a serious condition. Early diagnosis, treatment of infection and proper surgical management can improve the outcome and decrease complications.